Design, synthesis, biological evaluation and docking study of 4-isochromanone hybrids bearing N-benzyl pyridinium moiety as dual binding site acetylcholinesterase inhibitors (part II) - Wang, Jia; Wang, Chaolei; Wu, Zheng; Li, Xinnan; Xu, Shengtao; Liu, Jie; Lan, Qinying; Zhu, Zheying; Xu, Jinyi (Wiley, 2018)
A series of novel 4-isochromanone compounds bearing N-benzyl pyridinium moiety were designed and synthesized as acetylcholinesterase (AChE) inhibitors. The biological evaluation showed that most of the target compounds exhibited potent inhibitory activities against AChE. Among them, compound 1q possessed the strongest anti-AChE activity with an IC50 value of 0.15 nM and high AChE/BuChE selectivity (SI >5000). Moreover, compound 1q had low toxicity in normal nerve cells and was relatively stable in rat plasma. Together, the current finding may provide a new approach for the discovery of novel anti-Alzheimer’s disease agents.